A New Type of Banana Shape Bifunctional Monomer of Ester Chalcones - Zainab, Ngaini; Mei Chee, Chua; Lian, Chin Lim (Ibnu Sina Institute., 2014)
A synthesis of a new type of chalcone analogue banana-shaped liquid crystals compounds is described. The approach involved the reaction of hydroxyl chalcones with isophthaloyl dichloride to form benzene-1,3-dicarbonyl-bis-1-(4-alkoxyphenyl)-3-(4-hydroxylphenyl)prop-2-en-1-one (7a-c and 8a-c) having two chalcone units via esterification reaction. The hydroxyl chalcones, which differ in the length of alkyl group, CnH2n+1, where n= 10, 12 and 14 were synthesised via Claisen Schmidt condensation prior to the reaction with isophthaloyl dichloride. The reaction was a catalyst dependence. No sign of product was formed by employing NaH (60%). It was only occurred in the presence of NaH (95%) to afford banana shape bi-functional monomer of ester chalcone 7a-c and 8a-c. The synthesized compound was characterized by 1H and 13C Nuclear Magnetic Resonance (NMR), and Fourier Transform Infrared (FTIR).